UPAYA GURU MENUMBUHKAN PERILAKU BERTANGGUNG JAWAB SISWA DALAM BELAJAR DI MI MUHAMMADIYAH 12 NGAMPEL PONOROGO JAWA TIMUR - Muhammad Marzuqi; Ahmad Muslich; Ayok Aryanto (Universitas Muhammadiyah Ponorogo, 2020)
This research was conducted to know the factors that cause fifth-grade children to be less responsible in their learning at Madrasah Ibtidaiyah 12 Ngampel and the teacher efforts of the teacher in fostering responsible behavior in classroom children’s learning. This type of research is qualitative research with a case study approach. The subjects of this study were all students of grade V, totaling 14 students, the principal of the class teacher. Religion teacher and MADIN/TPA teacher. Data collection methods used included an interview, observation, and documentation. Meanwhile, the data analysis used included: data reduction, data presentation, and concluding data validation using triangulation and member checking techniques. The results of this study are as follows (1) the factor that causes less responsibility the learning of class children V Madrasah Ibtidaiyah 12 Ngampel, namely the ability of the student is low. The level of student awareness is low in the importance of learning responsibility and the lack of attention of parents toward children’s education. (2) teacher effort in fostering responsible behavior in learning for grade V student in Madrasah Ibtidaiyah 12 Ngampel, that is student introduced to the importance of responsibility in taking responsibility for learning and collaboration between the school and parent in caring for and educating children.